2017
DOI: 10.1007/s00421-017-3589-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of eccentric exercise with blood flow restriction on neuromuscular activation, microvascular oxygenation, and the repeated bout effect

Abstract: This study suggests that the neuromuscular and deoxygenation (i.e., metabolic stress) responses were considerably different between LI and LI-BFR groups; however, these differences did not lead to improvements in the RBE inferred by performing LI and LI-BFR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 70 publications
1
23
0
1
Order By: Relevance
“…The results regarding the differences in muscle excitation between LL and LL-BFR training demonstrated a significant increase in surface muscle EMG in favor of LL-BFR. The longitudinal changes which are reviewed in this work, resemble findings from cross-sectional studies looking at the acute effects of training with partial vascular occlusion (Kinugasa et al, 2006;Lauver et al, 2017Lauver et al, , 2019Husmann et al, 2018;Ilett et al, 2019;Kjeldsen et al, 2019). In a frequently cited study by Moritani et al (1992) participants were instructed to complete a 4-min bout of repeated intermittent isometric hand grip contractions (20% MVC) with one group having the blood flow restricted during the second minute (cuff pressure 200 mmHg).…”
Section: Muscle Excitationmentioning
confidence: 85%
See 1 more Smart Citation
“…The results regarding the differences in muscle excitation between LL and LL-BFR training demonstrated a significant increase in surface muscle EMG in favor of LL-BFR. The longitudinal changes which are reviewed in this work, resemble findings from cross-sectional studies looking at the acute effects of training with partial vascular occlusion (Kinugasa et al, 2006;Lauver et al, 2017Lauver et al, , 2019Husmann et al, 2018;Ilett et al, 2019;Kjeldsen et al, 2019). In a frequently cited study by Moritani et al (1992) participants were instructed to complete a 4-min bout of repeated intermittent isometric hand grip contractions (20% MVC) with one group having the blood flow restricted during the second minute (cuff pressure 200 mmHg).…”
Section: Muscle Excitationmentioning
confidence: 85%
“…Although a small number of previous investigations have already examined the magnitude of neuromuscular responses following LL-BFR training, these findings are conflicting with some studies reporting no differences between HL and LL-BFR (Sousa et al, 2017;Cook et al, 2018) and another study showing higher neural activation when training with HL only (Kubo et al, 2006). Similar inconsistent findings have been observed when comparing LL training with LL-BFR training (Thiebaud et al, 2014;Lauver et al, 2017;Oranchuk et al, 2019). This second comparison (LL vs. LL-BFR) is not less important, considering the common implementation of low-load regimens in clinical settings especially during the early phases of rehabilitation (Bousquet et al, 2018).…”
Section: Introductionmentioning
confidence: 89%
“…This is likely due to the hypoxic muscular environment generated during BFR and accelerated onset of fatigue [117]. Several studies have shown greater internal muscle activation with BFR exercise [119,120] relative to external load [121,122], which is greater than matched workload exercise without BFR [123,124]. Considering the importance of high threshold motor unit recruitment to the magnitude of EIH, early preferential recruitment of these motor units during low intensity BFR exercise may contribute to a hypoalgesia effect.…”
Section: Bfr Exercise and Hypoalgesiamentioning
confidence: 99%
“…Fatiguing low-load and/or high-volume resistance exercise has been shown to produce greater ATP turnover compared to traditional high-load resistance exercise (Gorostiaga et al, 2012 ; Ahtiainen et al, 2015 ). Furthermore, fatiguing low-load resistance exercise conducted with slow and tonic contraction phase or application of external restriction of blood flow to the exercising muscle, has been shown to impose a more pronounced decrease in tissue oxygenation compared to traditionally performed high- and low-load resistance exercise (Tanimoto and Ishii, 2006 ; Karabulut et al, 2014 ; Lauver et al, 2017 ). It therefore seems plausible that fatiguing low-load resistance exercise entail greater metabolic stress, to potentially accentuate mitochondrial biogenesis.…”
Section: Considerations On the Utilization Of Low-load Resistance Exementioning
confidence: 99%